Synthesis of high cation exchange capacity faujasite from high calcium fly ash - Thuadaij P. (INSInet Publications, 2015)
The use of high calcium fly ash probably can cause some negative effect to concrete. Therefore, an attempt for high calcium fly ash utilization would be one of challenged topic for waste management in Thailand. In this paper, the synthesis of faujasite zeolite from high calcium fly ash (FA) mixed with amorphous silica (AS) from rice husk ash and metakaolinite (MK) was carried out in this study. The study focused on the effect of SiO2/Al2O3 ratios of FA, AS and MK in the range of 3-5, on the faujasite zeolite formation. In addition, effects of the NaOH/(FA:AS) and NaOH/(FA:AS:MK) ratio (So/S), crystallization temperature and time which were varied as 1-1.6, 343-373 K and 6-96 h, respectively. The fusion followed by incubation methods were used for the synthesis. Faujasite zeolite was obtained at So/S of 1.0, 343 K of crystallization temperature and 24 h of crystallization time. The SiO2/Al2O3 ratios of 3.71 and 3.25 generated the faujasite formation containing 360 and 420 meq 100g-1 of cation exchange capacity, respectively. Specific surface areas were 233 and 398 m2g-1, respectively.